Analisis Faktor Kandungan Bakteri Escherchia Coli Air Sumur Gali Di Desa Pesisir Laut - Indrayadi, Indrayadi; Rafiun, Annajemin; Azis, Eyastuti; Pannyiwi, Rahmat; Misnarliah, Misnarliah; Basir, Anatasia A.; Idris, Idris; Sahabuddin, Sahabuddin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Water is a necessity of life that must be met to meet human needs, the need for water seems to never end, including for drinking, processing food, bathing, energy, transportation, agriculture, industry and recreation. The habit of students in Islamic boarding schools is to drink water directly from the source. Sources that do not meet the existing requirements and provisions can be inhabited by bacteria and can pollute the water, one of which is Escherichia coli bacteria. The purpose of this study was to determine the presence or absence of Escherichiae coli bacteria in dug well water in the coastal village of Sumpang Binangae. This research method is descriptive with a population of 4 dug wells in the coastal village of Sumpang Binangae, with a total sampling technique, data analysis with frequency distribution in percentage, data processing, coding tabulating and identification method of Escherichia coli bacteria with the MPN method. The results of the study from 4 samples tested there were 2 (50%) positive samples containing Escherichia coli bacteria with the number of bacteria 93 in the SG 2 code and >2400 in the SG 4 sample code. The conclusion of this study is that there are Escherichia coli bacteria in two samples from a total of 4 samples or a percentage of 50%.